Advances in multi-modality imaging for constrictive pericarditis and pericardial inflammation: role of imaging-guided therapy. (3rd April 2023) - Kafil, Tahir S; Wang, Tom Kai Ming; Agrawal, Ankit; Majid, Muhammad; Syed, Alveena B; Hutt, Erika; Alencherry, Ben; Cohen, Joshua A; Kumar, Sachin; Bansal, Agam; Griffin, Brian P; Klein, Allan L
ABSTRACT: Introduction: Constrictive pericarditis (CP) can result from uncontrolled inflammation of the pericardium. This can be due to various etiologies. CP can lead to both left- and right-sided heart failure with associated poor quality of life, so early recognition is key. The evolving role of multimodality cardiac imaging allows for earlier diagnosis and facilitates management to help mitigate this adverse outcome. Areas covered: This review discusses the pathophysiology of constrictive pericarditis, chronic inflammation and autoimmune etiologies, clinical presentation of CP, and advances in multimodality cardiac imaging for diagnosis and management. Echocardiography and cardiac magnetic resonance (CMR) imaging remain cornerstone modalities to evaluate this condition, whereas additional imaging modalities such as computed tomography and FDG-positron emission tomography can provide complementary information. Expert opinion: Advances in multimodality imaging allow for a more precision diagnosis of constrictive pericarditis. There has been a paradigm shift in pericardial disease management with advances in multimodality imaging, especially CMR, to detect subacute and chronic inflammation. This has enabled imaging-guided therapy (IGT) to both help prevent and potentially reverse established constrictive pericarditis.